Topological comparison and analysis of medium-voltage and high-power direct-linked PV inverter - Xing Zhang; Mingda Wang; Tao Zhao; Wang Mao; Yuhua Hu; Renxian Cao (CES Transactions on Electrical Machines and Systems, 2019)
Among all the renewable energy sources, the installed capacity of solar power generation is the fastest growing in recent years, so photovoltaic (PV) power generation still has great market potential. Compared with low-power systems, large-scale PV systems are more commercially attractive, because they can reduce the cost of the system per watt. The PV inverters with centralized and string structure have been applied in large-scale PV plant, but it is difficult to further increase the voltage and power levels for a single converter. In addition, the line-frequency isolation transformer requires a large amount of materials and has a large volume and weight. Therefore, it is a current trend for large-scale PV system to increase the voltage and power levels to directly connect to the medium-voltage power grid. Based on this, this paper investigates and compares several topologies of PV inverters without line-frequency transformer, including the MMC structure and the three-phase cascaded H-bridge (CHB) structure, which are able to directly connect to the 35kV medium-voltage power grid, and can not only make the voltage and power levels higher, but also further reduce the cost and volume of the whole system.